Using codesign to develop a culturally tailored, behavior change mHealth intervention for indigenous and other priority communities: A case study in New Zealand. Issue 4 (2nd November 2018) - Verbiest, Marjolein E A; Corrigan, Callie; Dalhousie, Sally; Firestone, Ridvan; Funaki, Tevita; Goodwin, Debbie; Grey, Jacqui; Henry, Akarere; Humphrey, Gayl; Jull, Andrew; Vano, Mereaumate; Pekepo, Crystal; et al.
Abstract : Co-design methods and behaviour change theory were integrated to create a smartphone app to support health and wellbeing in Maori and Pasifika communities in New Zealand. Abstract: The obesity rate in New Zealand is one of the highest worldwide (31%), with highest rates among Māori (47%) and Pasifika (67%). Codesign was used to develop a culturally tailored, behavior change mHealth intervention for Māori and Pasifika in New Zealand. The purpose of this article is to provide an overview of the codesign methods and processes and describe how these were used to inform and build a theory-driven approach to the selection of behavioral determinants and change techniques. The codesign approach in this study was based on a partnership between Māori and Pasifika partners and an academic research team. This involved working with communities on opportunity identification, elucidation of needs and desires, knowledge generation, envisaging the mHealth tool, and prototype testing. Models of Māori and Pasifika holistic well-being and health promotion were the basis for identifying key content modules and were applied to relevant determinants of behavior change and theoretically based behavior change techniques from the Theoretical Domains Framework and Behavior Change Taxonomy, respectively. Three key content modules were identified: physical activity, family/ whānau [extended family], and healthy eating. Other important themes included mental well-being/stress, connecting, motivation/support, and health literacy. Relevant behavioral determinants were selected, and 17 change techniques were mapped to these determinants. Community partners established that a smartphone app was the optimal vehicle for the intervention. Both Māori and Pasifika versions of the app were developed to ensure features and functionalities were culturally tailored and appealing to users. Codesign enabled and empowered users to tailor the intervention to their cultural needs. By using codesign and applying both ethnic-specific and Western theoretical frameworks of health and behavior change, the mHealth intervention is both evidence based and culturally tailored.